Synthesis of electron beam irradiated hydrogel beads for disaster relief applications - Oh, Jessica Si Jia (2012)
When natural disaster occurred without warning, it destroyed almost everything including water facilities and infrastructures. Restoring infrastructures or transporting necessities into affected areas would take a period of time. Light-weight, ease of use and ease of transport, water purification method was needed in disaster area to provide potable water. This research focuses on the synthesis of electron beam irradiated hydrogel beads that would be suitable for disaster relief application. Biocompatible, non-toxic and biodegradable materials alginate and chitosan were used to fabricate hydrogel beads. The effect of electron beam radiation on swelling capability, reusability and bacteria exclusion capability of the hydrogel were determined and was found to play a dominant role in determining the swelling capability, reusability and bacteria exclusion capability of the hydrogel beads. Hydrogel beads irradiated with electron beam of dose 5 Mrad gives highest swelling ratio percentage of 231.4 % and hydrogel beads irradiated with dose of 15 Mrad were able to remove bacteria up to 86.7 % after three cycles of absorption/compression. Hydrogel beads synthesized were capable of reuse up to a maximum of only two times, further optimization is needed to produce hydrogels of higher mechanical properties to meet the needs of disaster relief application. Preliminary morphological characterization of hydrogel beads were provided with the use of optical microscopy and remarkable difference was observed in the surface structure between swelled and unswelled hydrogel beads. Higher magnification analysis with use of SEM was not possible as hydrogel beads dehydrated under vacuum condition in the SEM chamber.